The perception towards wasiyyah (will) among Malay Society / Muhammad Yunus Muda - Muda, Muhammad Yunus (Faculty of Business Management, 2017)
Wasiyyah or will is one of the issues faced by Malaysian especially Malay society. Previous studies on these issues have been conducted only on general Muslim population, not on specific Malay Muslims. Thus, this study is to determine what is the factor influence most of Malay society to make Wasiyyah (will) and their perception on Wasiyyah. There are unclaimed cash and assets left by deceased due to the absence of estate planning. Specifically, 90 percent of the Malay society do not write a will because of several reasons. The independent variables in this study are attitude, subjective norm, and knowledge. The study will use primary data which data will be collected through the distribution of questionnaires and it will regress by SPSS using multiple regressions. Based on the result of previous researchers, knowledge will be the most influential factor for employees to make Wasiyyah. From the findings in this research, the result revealed that only attitude and knowledge are significant with Malay perception on Wasiyyah (will) and it shows that attitude is the most important factor that influences Malay perception on Wasiyyah (will).